Effects of yeast culture on growth performance, antioxidant capacity, immune function, and intestinal microbiota structure in Simmental beef cattle - Li, Xueqiang; An, Nan; Chen, Hui; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
IntroductionAs functional feed additives, yeast cultures have been applied in animal husbandry and shown a wide range of good efficacy. This paper aimed to evaluate the effects of yeast culture (YC) on the growth performance, antioxidant capacity, immune function, and intestinal microbiota structure in beef cattle.MethodsForty Simmental bulls were randomly divided into two groups, including the control group fed with Total mixed ration (TMR) and YC group fed with TMR supplemented with 2% YC, for 60 days. Serum samples were collected on the 1st, 30th, and 60th days, respectively, while feces 3 days before the end of the test.ResultsResults showed that YC addition significantly elevated average daily gain and reduced feed to weight ratio of beef cattle. The enzyme activities of total superoxide dismutase, total antioxidant capacity, and glutathione peroxidase in the serum in YC group obviously increased, while the malondialdehyde content distinctly decreased. Furthermore, YC feeding significantly enhanced the immunoglobulin G (IgG), IgA, IgM levels, lysozyme content, alkaline phosphatase activity, as well as the contents of interleukin-1β (IL-1β), IL-6, and interferon-γ in the cattle serum. The Shannon and Observed species indexes of fecal samples in YC group were remarkably higher than those in the control group, with the former group exhibiting a significant increase in the relative abundance of Paraprevotellace_CF231 and Peptostreptococcaceae_Clostridium at the genus level, while the relative abundance of Spirochaetaceae_Treponema decreased significantly. Moreover, the abundance of Clostridium and CF231 was positively associated with the levels of serum antioxidant capacity and immune function indicator contents.DiscussionIn conclusion, YC could obviously improve the growth performance, antioxidant capacity, immune function, and intestinal microbiota structure in Simmental beef cattle. These results provide a theoretical basis for the clinical application of such yeast fermented preparations in beef cattle husbandry.